PENGARUH LINGKUNGAN KERJA TERHADAP PRESTASI KERJA PEGAWAI DI KANTOR CAMAT NANGA PINOH - Dedy Kurniawan E.42008058 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
The purpose of this study was to identify and analyze: 1) the effect of the physical workenvironment on Nanga Pinoh Head Office, 2) effect of job performance on Nanga Pinoh HeadOffice; 3) Effect of physical work environment on job performance at the Head Office of NangaPinoh. This study was chosen because the authors see the phenomena that lead to the performanceof the employee to be down, in particular the problems caused by the work environment. Thisstudy includes the type of quantitative research to test the hypothesis. The population in this studywere all employees at Head Office Nanga Pinoh totaling 25 people. The technique used is asaturated sampling technique that takes all members of the population as a sample. Data collectiontechniques using a questionnaire that had been tested in advance and test the validity and reliabilitytesting. The data analysis technique used is a simple regression analysisThe results of a simple regression analysis to obtain the equation Y = 0.391X + 12 190, whichmeans job performance is influenced by the work environment. The results of the regressionanalysis also obtain the value of the coefficient of determination (R2) of 0891, this means that89.1% variable job performance is influenced by the work environment. The remaining 10.9%explained by other variables not examined, such as education, work discipline, reward andmotivation. Conclusions: 1) implementation of the physical work environment at Head Office inNanga Pinoh say pretty good by most respondents. Respondents who stated they were quite good,that amounted to 16 respondents (64%). 2) Work performance in the implementation of NangaPinoh Head Office in fairly good state of respondents said pretty well totaled 16 respondents(64%). 3) The work environment positive effect on employee job performance Nanga Pinoh HeadOffice. This result is evident from the results of the t test were obtained thitung X = 13 701received at significance level of 5% and F test results were obtained for 187 728 Fhitung acceptedat significance level of 5%. Keywords: Physical Work Environment, Work interpretation.